Characterization of a profile of residual soil from granite combining geological, geophysical and mechanical testing techniques - A. Viana da Fonseca (2006)
This paper summarizes the results of an experimental site investigation and characterization survey, on a residual (saprolitic) soil from granite, in the framework of a research project led by the Faculty of Engineering of the University of Porto (FEUP). This project aims at characterizing these unusual soils in the context of the development of an International Prediction Event (Class A) on the behaviour of different types of piles. A very extensive site characterization campaign, including a large variety of in-situ tests and field methods, has been held. These investigations comprised the application of several geophysical borehole and surface methods, namely P- and S-wave seismic refraction, reflection, cross-hole (CH), downhole (DH), electrical resistivity imaging and ground probing radar (GPR), as well as mechanical tests, namely SPT, CPT and DMT, among others. The site is geologically formed by an upper layer of heterogeneous residual granitic soil, overlaying rather weathered granite contacting a gneissic migmatite. Direct and indirect results from some of the referred surveys were compared between them and with some of the available geological and geotechnical information, namely those obtained from seismic, electrical and GPR profiles, conducted adjacent to three boreholes in which undisturbed soil samples were collected previously to geophysical data acquisition. In addition, a comprehensive laboratory testing program was carried out using the collected undisturbed samples. A discussion of the obtained results is hereby presented, giving emphasis to the correlations encountered between the different tests, specific of saprolitic soils with weak relic structures.